Case Studies in Early Modern Intelligence - Graf, Tobias P.; Backerra, Charlotte (Journal of Intelligence History, 2022)
This introduction to the special issue ‘Case Studies in Early Modern European Intelligence’ provides an overview of scholarship on the history of intelligence in the early modern period. Examining outstanding research contributions to the field, it highlights the potential of early modern European history to contribute to a refinement of the methodology and theory of intelligence history as a whole. In light of the contributions made by the articles collected in this special issue, we argue that intelligence history as a discipline will benefit from an increased dialogue between scholars working on different periods. We therefore invite historians of intelligence to study the early modern period and historians of the early modern period to study intelligence.<br
Keywords: Spionage; Geheimdienste; intelligence; Frühe Neuzeit; Europa